Nilai-nilai Pendidikan Multikultural dalam Kearifan Lokal Masyarakat Maluku - Abidin Wakano (IAIN Ambon, 2019)
The research aims to describe and explain the: 1. local wisdom In the culture of Maluku people as the power of social integration and brotherhood in the multicultural context of Maluku people. 2. The values of multicultural education in culture Pela, Gandong, Famili, Badati, Masohi, Ma’anu. This research uses a qualitative deskrptive method with a content analysis technique (content analysis, Through two steps of procedure, namely: First. Procurement or data collection of multicultural education values in the local wisdom of the Maluku people. Second. Data validation using semantic validation patterns to measure the solitude and depth of symbolic meanings associated with the context of multicultural values in the local wisdom of the Maluku community. The results of this study showed Local wisdom forms that contain the value of fraternity and become the power of social integration, inter-siwalima The Monodualistic Cultural roots, then culture pela, gandong, famili, And each other culture and cooperation such as culture badati, masohi, ma’anu. The values of the Muliticular education in the forms of the wisdom of life between Values understand each other's differences, Respect each other, Love one another, protect each other, sustain one another, and support each other, As the fact or reflection of Multikulturl education, respect for others and respect for self.